ANALYSIS OF IMPLEMENTATION OF PSAK NO. 73 ON FINANCIAL PERFORMANCE IN TRANSPORTATION SUB SECTOR COMPANIES - Nur Afni Yunita; Rany Gesta Putri Rais; Muhammad Yusra; Risky Putri Amalia (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to examine the impact of the implementation of PSAK No. 73 on financial performance. The sample in this study is the transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The sampling technique used was purposive sampling so that a sample of 27 companies. The results show that PSAK No. 73 as a proxy for liabilities has no significant effect on profitability and solvency ratios. PSAK No. 73 which is proxied by assets has no significant effect on the ratio of profitability and solvency. PSAK No. 73 which is proxied by equity does not have a significant effect on the profitability ratio, but has a significant effect on the solvency ratio. The coefficient of determination in this study shows a value of 0.0234 for the profitability ratio. This means that the application of PSAK No. 73 has a 2% role in the profitability ratio. As for the solvency ratio, the coefficient of determination in this study shows a value of 0.503. This means that the application of PSAK No. 73 has a role of 50.3% to the profitability ratio.